PENGARUH GAYA EVALUASI ATASAN TERHADAP TEKANAN DAN KEPUASAN KERJA BAWAHAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIBEL MODERATING - Aida Nahar (Universitas Islam Nahdlatul Ulama Jepara, 2004)
AbstractMost of accounting studies had examined the relationship between the evaluative style of superiors and work related attitudes of subordinates. The result, however, showed that relationships were not consistent. These conflicting evidence reflected the influence of conti11ge11cy variables in the effect the relationship between the evaluative style of superiors and work related attitudes of subordinates. This paper extends previous work in the area of supervisory style as it pertains to the use of budgetary information for performance evaluation. This study examined influence of the evaluative style of superiors on job related tension and job·satisfaction with organization's culture as moderate variables. This study focused exclusively on the superior's budgetary pe1formance evaluation style a11d used multiple regression's model.Based on the fifty production and marketing managers questionair respon of a number ofmanufacturing companies in Central Java, the results of the study, showed that budgetary performance evaluation style in the organization's culture that job oriented, made high job related tension and low job satisfaction of subordinates. Keywords: Budgetary pe1formance evaluation style, Job related tension, Job Satisfaction 01 ganization s culture